Pedro Cerezo’s Quixote, or the other Modernity - Higuera Espín, Javier de la (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
Pedro Cerezo has dedicated a very extensive work to the study of Spanish thought as well as to the study of modern and contemporary philosophy, but it has been above all in his reading of the Quixote, culminating in his recent book The Quixote and the Adventure of Freedom (2016), where he has productively crossed those two lines of thought, the one that led him to the question of «thinking in Spanish» and the one that led him to «the question of modernity», providing important keys that help to complete our understanding of modernity and to productively rethink the question of the function and possibility of philosophy today. This article deals with the role that, according to Cerezo, the Quixote plays in the constitution of modernity by reconstructing his idea of a literary «Spanish thought» capable of bringing new possibilities to modernity.